Ecological Modernization Theory (EMT): Antecedents and Successors - Dulcimar José Julkovski; Simone Sehnem; David Bennet; Michel Leseure (Universitas Pasundan, 2021)
This study consolidates the state of academic research on the Ecological Modernization Theory (EMT). The EMT starts from a sociological perspective and enters into a series of political and economic factors that are considered crucial under the aegis of processes and practices. EM predicts that under political, economic, and technological conditions, competition among capitalists can be redirected to achieve eco-efficiency of pollution prevention. Based on a literature review from across 26 years, the study presents an overview of the evolution of the theme, background, and future perspectives. Using the databases Scopus, Web of Science, and Science Direct, a sample of 291 studies was mapped, which were read in full. Content analysis was conducted to abstract the current panorama of the theory of ecological modernization and to infer trends of the progress of the subject. The originality/value of this study is that we integrate diverse research perspectives into a comprehensive multidimensional structure of EM, with the purpose of analyzing the antecedents, artifacts associated with theory, method, types of studies developed, constructs explored together with the theory of EM and subcategories context, relevant stakeholders, technological innovations, and public policies. As future perspectives for studies, we suggest aligning EMT with circular economy, industry 4.0, and management information systems based on big data.